Locomotor control in the long jump approach run in young novice athletes - Panteli, F. N.; Theodorou, A.; Pilianidis, T.; Smirniotou, A. (Journal of Sports Sciences, 2014)
We examine the presence of visually regulated control in young, novice long jumpers as they approach the takeoff board. The approach run of 27 novice jumpers (age 12-13 years) practising jump training for a short period was video-recorded during competition. Findings revealed that young, novice participants adjust the length of the final steps of their approach run, suggesting the presence of visual control. Step regulation commenced on the fifth and fourth step from the board for boys and girls respectively. Their pattern of footfall variability was found to be comparable to that of skilled long jumpers, although young, novice participants presented slightly higher variability. It appears that even a limited period of jump training may contribute to a more consistent run-up as well as to smaller takeoff error, offsetting the limitations imposed by the partially developed cognitive abilities and perceptual awareness of young athletes.